Monoballism Associated with Newly Onset Ketotic Hyperglycemia - Dilek Ersil Soysal; Barıs Gelen; Sezin Hızar; Mete Pekdiker; Ebru Tekesin; Yesim Beckmann; Volkan Karakus (Case Reports in Endocrinology)
Movement disorders as the initial symptoms of diabetes mellitus are rare. Here, we describe one of these rare manifestations of primary diabetes: a case of newly diagnosed diabetes mellitus in an old-age female patient with transient monoballismus during an episode of ketotic hyperglycemia.